Evaluasi Usability Website Sistem Informasi Pelayanan Perizinan Banyumas (SIPANJIMAS) Menggunakan Metode System Usability Scale (SUS) - Kunaslimah Zainurrohmah; Daniel Yeri Kristiyanto; Darmansah Darmansah (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Sistem Informasi Pelayanan Perizinan Banyumas (SIPANJIMAS) is one of the services licensing provided digitally by DPMPTSP Banyumas Regency. In its development, there were bugs in e-mail synchronization and errors in several features in SIPANJIMAS. The problems found show that the services and information by DPMPTSP Banyumas Regency to users are still not as suitable as needed, so it is necessary to analyze the usefulness of the SIPANJIMAS website. The method used in this study is the System Usability Scale (SUS). The results obtained are SIPANJIMAS website has an average usability of 59,75 which is included in category â€œCâ€ with the description â€œQuite Decentâ€.